2020
DOI: 10.3390/microorganisms8040521
|View full text |Cite
|
Sign up to set email alerts
|

The Response to Oxidative Stress in Listeria monocytogenes Is Temperature Dependent

Abstract: The stress response of 11 strains of Listeria monocytogenes to oxidative stress was studied. The strains included ST1, ST5, ST7, ST6, ST9, ST87, ST199 and ST321 and were isolated from diverse food processing environments (a meat factory, a dairy plant and a seafood company) and sample types (floor, wall, drain, boxes, food products and water machine). Isolates were exposed to two oxidizing agents: 13.8 mM cumene hydroperoxide (CHP) and 100 mM hydrogen peroxide (H2O2) at 10 °C and 37 °C. Temperature affected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…The phenotype of the ntrC mutant indicated that NtrC was not only absolutely required for nitrogen metabolism in P. stutzeri, but also related to optimal resistance to oxidative stress. The ntrC mutant showed signi cant upregulation of oxidative stress response genes, especially katB, which is the most pivotal enzyme for oxidizing agent CHP (Manso et al 2020). Bioinformatics analysis revealed one NtrC binding site to the promoter region of katB, indicating that KatB is the potential target regulated by NtrC.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype of the ntrC mutant indicated that NtrC was not only absolutely required for nitrogen metabolism in P. stutzeri, but also related to optimal resistance to oxidative stress. The ntrC mutant showed signi cant upregulation of oxidative stress response genes, especially katB, which is the most pivotal enzyme for oxidizing agent CHP (Manso et al 2020). Bioinformatics analysis revealed one NtrC binding site to the promoter region of katB, indicating that KatB is the potential target regulated by NtrC.…”
Section: Discussionmentioning
confidence: 99%
“…Well-established L. monocytogenes ATCC 7644 strain was chosen to enable international comparison of results between studies. Research by Manso et al (2020) showed that different Listeria monocytogenes isolates differ in susceptibility for environmental stress; therefore, other listeria strains should be further investigated in the future to accomplish knowledge how different strains react to nanomaterials and illumination.…”
Section: Discussionmentioning
confidence: 99%
“…In order to withstand exposure to oxidizing agents, e.g., sodium hypochlorite, cells must activate mechanisms to repair damages of proteins, the cytoplasmic membrane, and nucleic acids. Listeria monocytogenes under oxidative stress activates a survival strategy that includes the expression of sigB , cold and heat shock proteins, proteases (ClpC, ClpP, and GroEL), and ROS detoxification systems ( Manso et al, 2020 ). ROS detoxification systems include superoxide dismutase (Sod), catalase (Kat), and alkylhydroperoxidase (AhpCF; Bucur et al, 2018 ).…”
Section: Stress Factors In the Food Processing Environmentmentioning
confidence: 99%
“… Manso et al (2020) have shown that oxidative stress is temperature-dependent. The lower temperature increased oxidative stress response.…”
Section: Stress Factors In the Food Processing Environmentmentioning
confidence: 99%
See 1 more Smart Citation